My brother bit me [videorecording] : parenting sibling (Chicago, I.L. : Learning Seed)
Parenting one child is a challenge, but add a second child and new problems spring up faster than a parent can say "help." Learn important parenting skills for multiple-child families, including how to correct and compliment children while avoiding favoritism